Prevalence and Risk Factors of Bovine Mastitis in Southern Zone of Tigray, Northern Ethiopia - Adehanom Baraki; Teshale Teklue; Tesfay Atsbha; Temesgen Tesfay; Solomon Wayou (Veterinary Medicine International)
Mastitis is the most common disease of adult dairy cattle. The disease continues to be one of the most perplexing and costly diseases of dairy cattle. The present study was conducted to detect bovine mastitis cows and identify potential risk factors for the distribution of bovine mastitis of smallholder dairy farmers using the California mastitis test. A cross-sectional study was conducted from September 2013 to May 2015 in the southern zone of Tigray, Northern Ethiopia, on 146 head of randomly selected cattle, of which 99 (67.8%) were crossed zebu and 47 (32.2%) pure local zebu using the California mastitis test and questionnaire. The overall prevalence was 65 (45.5%), of which 72.3% of crossed local and 27.69% of local zebu were found positive for the CMT test. The investigated risk factors were the season of lactation (OR = 0.510, CI = 0.208–1.247, P=0.140), washing hands between consecutive milking events (OR = 0.354, CI = 0.146–0.856, P=0.021), and history of previous mastitis (OR = 0.441, CI = 0.226–0.858, P=0.016), which had significant (P<0.05) effect on the present prevalence of bovine mastitis in the study area. A high prevalence of bovine mastitis was observed in the southern zone of Tigray. The summer season of lactation and not washing hands between consecutive milking of cows were significant mastitis causation risk factors in addition to the history of previous mastitis disease history.